1982
DOI: 10.1111/j.1432-1033.1982.tb06820.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidase and Oxygenase Function of the Microsomal Cytochrome P450 Monooxygenase System

Abstract: The rates of the NADPH-dependent formation of superoxide radicals and hydrogen peroxide have been measured in liver microsomes from phenobarbital-pretreated rats. Correcting a quenching of 0; radicals by microsomes, a stoichiometry of 0; to Hz02 close to 2 : 1 was obtained. This, and the fact that pseudo-substrates of microsomal cytochrome P450 like perfluoro-n-hexane and perfluorinated cyclohexane did not increase H2Oz formation in a catalase-inhibited assay, rules out a two-electron reduced oxygen species as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(83 citation statements)
references
References 41 publications
(33 reference statements)
1
79
0
3
Order By: Relevance
“…This may account for the failure of substrates for mixed-function oxidases to enhance ROS formation, either in the presence or absence of NADPH. Other reports have also indicated that these enzymes can be more potent in ROS production in the absence of exogenous substrates [32,33]. Ethanol-inducible cytochrome P450 IIEI oxidase is especially capable of effecting oxidative events since it has a high rate of oxidase activity in the absence of substrate [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This may account for the failure of substrates for mixed-function oxidases to enhance ROS formation, either in the presence or absence of NADPH. Other reports have also indicated that these enzymes can be more potent in ROS production in the absence of exogenous substrates [32,33]. Ethanol-inducible cytochrome P450 IIEI oxidase is especially capable of effecting oxidative events since it has a high rate of oxidase activity in the absence of substrate [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…CYP1A1 is an enzyme involved in bioactivation of procarcinogens and during such process it produces reactive metabolites and ultimately leads to oxidative stress (Whitlock 1999). CYP450 during its metabolic cycling results in the formation of H 2 O 2 and hydroxyl radicals (Ingelman-Sundberg and Johansson 1984;Kuthan and Ullrich 1982). Thus it results in an atmosphere of oxidative stress, a state of imbalance between intracellular ROS and antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
“…Small amounts of the superoxide anion radical (O 2 ·̄ ) can be produced from decay of the oxygenated P450 complex, while hydrogen peroxide (H 2 O 2 ) can form from either dismutation of O 2 ·̄ or from decay of the peroxy P450 complex (8)(9)(10). ROS have been implicated in many of the major diseases that plague mankind, including the toxicity of O 2 itself; hyperbaric O 2 ; ischemiareperfusion injury; cardiovascular diseases; atherosclerosis; carcinogenesis; diabetes; neurodegenerative diseases, including Parkinson's disease and Alzheimer's disease; toxicity of heavy metals, e.g., iron; asbestos injury; radiation injury; vitamin deficiency; drug (e.g., redox cycling agents) toxicity; aging; inflammation; smoking toxicity; emphysema; and toxicity of acute and chronic ethanol treatment (11)(12)(13)(14)(15).…”
Section: Introduction-cytochrome P450 Oxidative Stress and Alcoholimentioning
confidence: 99%